Long-term visual field evaluation of trabeculectomy patients with a mean intraocular pressure below 15 mmHg - Marina Rocha; Jayter Silva Paula; Cassia Senger; Tiago Santos Prata; Fábio Nishimura Kanadani; Bruno de Barros Massote; Vitor Porto de Souza; Ana Cláudia Alves Pereira; Marcos P. Ávila; Leopoldo Magacho (PLoS ONE, 2026)
The purpose of this multicenter, longitudinal, retrospective, observational study was to evaluate the long-term visual field (VF) outcomes of glaucoma patients with a mean intraocular pressure (IOP) of less than 15 mmHg who underwent trabeculectomy (TRAB). Patients who underwent TRAB with at least 3 years of follow-up were divided into two groups: G1 (mean postoperative IOP between 6 and 9 mmHg) and G2 (mean postoperative IOP between 10 and 14 mmHg). A total of 49 eyes from 47 patients were included in G1, and 111 eyes from 90 patients were included in G2. The mean follow-up time was 4.72 ± 2.72 years in G1 and 4.63 ± 2.46 years in G2 (p = 0.832). The mean IOP was 7.88 ± 1.06 mmHg in G1 and 11.83 ± 1.41 mmHg in G2 (p < 0.001). The mean progression rate according to the mean deviation (MD) of the VF was −0.25 ± 1.09 dB/year in G1 and −0.27 ± 1.16 dB/year in G2 (p = 0.786). The changes in the visual acuity or VF indices over time were nonsignificant between the groups (p > 0.05 for all). TRAB is a safe procedure with mean IOPs either in the single digits (i.e., between 6 and 9 mmHg) or between 10 and 14 mmHg.